BIOETHANOL PRODUCTION FROM CELLULOSE IN RED ALGAE Gracilaria verrucosa BY SEPARATED HYDROLYSIS AND FERMENTATION SYSTEM USING Trichoderma viride AND Zymomonas mobilis - AHYAR AHMAD (International Journal of Pharma and Bio Sciences, 2014)
In this study, renewable marine cellulose from red algae Gracilaria verrucosa was utilized for the production of bioethanol. Bioethanol from the red alga cellulose was produced by the enzymatic hydrolysis and fermentation methods and the conversion value of the cellulose in Gracilaria verrucosa was estimated. Trichoderma viride fungus and Zymomonas mobilis bacterium were used for enzymatic hydrolysis and bioethanol fermentation, respectively. Enzymatic hydrolysis and fermentation optimization were carried out by varying pH and period of hydrolysis or fermentation. Research results indicate that the optimum condition of the enzymatic hydrolysis cellulose is obtained at pH 5.5 in 6 days, whereas the optimum condition of bioethanol fermentation is obtained at pH 6.0 in 7 days. The bioethanol concentration as measured by Gas Chromatography, showed that one kilogram of cellulose in Gracilaria verrucosa produces 23.01% bioethanol with the concentration of 29.60%